Analisis Kelayakan Usaha dengan Metode Diskonto dan Tanpa Diskonto: Studi Kasus UMKM Kedai Sera - Prabumulya, Rizkillah Aji; Nitisara, Naurah Wafa; Clara, Dinda; Aurelia, Sabila; Liliany, Azzahra Wani; Dian Fajarini (Goodwood Publishing, 2025)
This study aims to analyze the business feasibility of the Kedai Sera MSME located in Bandar Lampung City using both discounted and non-discounted methods. A descriptive quantitative approach was applied, utilizing primary data in the form of Kedai Sera’s annual financial statements for the period 2018–2024. The non-discounted method includes analysis using Payback Period, Break-Even Point (BEP), and Revenue-Cost (R/C) Ratio. Meanwhile, the discounted method employs Net Present Value (NPV), Internal Rate of Return (IRR), and Benefit-Cost Ratio (B/C) as indicators. The analysis results show that based on the non-discounted method, the business has a Payback Period of 2 years, a BEP of 1,530 units, and an R/C Ratio of 3.27, indicating that the business is feasible and efficient to operate. Furthermore, using the discounted method, the NPV is IDR 211,434,376 and the IRR is 31.9824%, which exceeds the discount rate of 11.25%, indicating financial feasibility. The Net B/C Ratio is < 1, suggesting that Kedai Sera’s business is feasible for development.